KNOWLEDGE, ATTITUDE, AND PRACTICES REGARDING INFECTION CONTROL AMONG UNDERGRADUATE DENTAL STUDENTS - Kumar Mp, Santhosh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To assess the level of knowledge, attitudes, and practices regarding infection control procedures among undergraduate dental students. Methods: A validated questionnaire of 23 questions regarding the basic knowledge, attitude, and practices regarding infection control in dental clinics was distributed among 150 students randomly belonging to third year, final year, and internship (fifth year trainee) of undergraduate dental program in Saveetha Dental College and Hospital, Saveetha University, Chennai. The data extracted were tabulated, statistically analyzed, and results obtained. Results were calculated on the basis of frequency and percentages using SPSS. Results: Nearly, 81.3% of students agreed that disinfection of dental clinic is important to prevent cross-infection among patients and dental personnel. 94.6% of dental students agreed that proper isolation during treatment is important for infection control in dentistry. 92% were aware of post-exposure prophylaxis against hepatitis B virus (HBV). 53.3% of them answered that HBV infection has the highest risk of transmission in the dental setting. 88% of students use gloves, face mask, head cap, gown always. 65.3% of dental students were willing to treat patients with infectious diseases after following universal/standard precautions. Conclusion: Dental students in this study have a good level of knowledge and positive attitudes about infection control. However, the knowledge acquired must be transferred into daily practice. Continuing education programs and refreshing courses regarding cross infection control procedures are necessary to update the knowledge of dental practitioners. Keywords: Infection control, Knowledge, Dental students, Dental safety, Practices, Hepatitis B virus.